Roles of E3 Ubiquitin-Ligases in Nuclear Protein Homeostasis during Plant Stress Responses - Serrano, Irene; Campos, Laura; Rivas, Susana (Frontiers in Plant Science, 2018)
Ubiquitination, the reversible protein conjugation with ubiquitin (Ub), is a post-translational modification that enables rapid and specific cellular responses to stimuli without requirement of de novo protein synthesis. Although ubiquitination also displays non-proteolytic functions, it often acts as a signal for selective protein degradation through the ubiquitin-proteasome system (UPS). In plants, it has become increasingly apparent that the UPS is a central regulator of many key cellular and physiological processes, including responses to biotic and abiotic stresses. In the nucleus, protein regulation via the UPS orchestrates gene expression, genome maintenance and signal transduction. Here, we focus on E3 Ub-ligase proteins as major components of the ubiquitination cascade that confer specificity of substrate recognition. We provide an overview on how they contribute to nuclear proteome plasticity during plant responses to environmental stress signals.